CONSISTENCY OF COVID-19 VACCINATION POLICY IN EFFORTS FOR EQUALITY OF VACCINE ADMINISTRATION (Journal of Governance and Development (JGD), 2022)
The handling of the COVID-19 pandemic has entered a new stage. Various policies and regulations in an effort to handle and break thechain of the spread of COVID-19 have been implemented by the government. These efforts include the PSBB policy, Transitional PSBB, PPKM, Micro PPKM, Emergency PPKM (Java-Bali) which had been implemented, Large- Scale Social Restrictions, Provision of activities that cause crowds, implementation of health protocols, and until now has entered the stage of policy regarding the COVID-19 vaccination. The vaccination policy has been contained in the Minister of Health Regulation Number 10 of 2021 concerning the Implementation of Vaccination in the context of Combating the 2019 Corona Virus Disease (COVID-19) Pandemic. The result of this research is with reference to the Perpres and Permenkes and when viewed from the implementation variables proposed by the theory of George C. Edwards III, which states that the effectiveness of policy implementation can be seen from the four variables that support the implementation of policies, namely: Communication, Resources, Disposition, and Bureaucratic Structure. So by reviewing these variables, that the implementation of the policy of the implementation of vaccination in Indonesia has been running quite well, and there are still various obstacles found both in its implementation and in the communication of the policy, so that there are still various perspectives that cause debate with the implementation of the vaccine policy. So that the consistency of the government in efforts to provide equal distribution of vaccinations in Indonesia is still running consistently even though in some remote areas the system and reporting of data on the implementation of the vaccination is still unknown.